Analysis of Qur'an Interpretation Methodology in Tahfidz Al-Fath Learning Module Volume 1,2,3,4 at Ar Rafi' Drajat Elementary School - Jubaedah, Siti; Najihah, Bannan Naelin (Journal of Ulumul Qur'an and Tafsir Studies, 2024)
Learning to memorize the Qur'an has an important role in Islamic education, especially in forming a generation that has a close relationship with the holy book as a religious guide. Learning modules that are structured and accompanied by appropriate interpretation methodologies can increase students' understanding and motivation in memorizing the Qur'an. Ar Rafi' Drajat Elementary School has implemented the Tahfizh Al-Fath module which involves a concise explanation of the verses. Tafsir Alqur'an methodology is a systematic procedure followed in an effort to understand and explain the meaning of Alqur'an content and is the most important component in interpreting Alqur'an. In the interpretation of the Qur'an, there are 4 kinds of methods that have developed , namely tahlili, ijmaly, muqarran, and maudhu'i. Each of these methods has its own criteria. Each of these methods has its own criteria. This study aims to determine the Tahfizh Al-Fath method in tahfizh learning at Ar Rafi' Drajat Elementary School and to determine the methodology of interpreting Alqur'an in the Tahfizh Al Fath learning module at Ar Rafi' Drajat Elementary School. This research uses a mixed method approach between literature study and field study with descriptive qualitative analysis using discourse analysis techniques. This study found that the stages of Tahfidz Al-Fath at Arrafi' Drajat Elementary School include listening, understanding, memorizing, practicing, and preaching the verses of the Qur'an, as well as purifying themselves through continuous understanding and practice. The Tahfidz Al-Fath module itself uses interpretation methodology with ijmaly style and has bil ma'tsur interpretation sources.